Osteoporosis in primary biliary cholangitis: from cholestasis to fracture prevention - Andrzejuk, Aleksandra; Rogalska, Magdalena; Rogalski, Paweł; Flisiak, Robert (Clinical and Experimental Hepatology, 2026)
Primary biliary cholangitis (PBC) is a chronic autoimmune cholestatic liver disease characterized by immune-mediated injury to the small intrahepatic bile ducts, culminating in impaired bile flow and, over time, progressive cholestasis, ductopenia, and biliary cirrhosis. Osteoporosis is a systemic skeletal disorder characterized by increased bone fragility, decreased bone mineral density, deterioration of bone microarchitecture, and increased fracture risk. In PBC, the most important risk factor for osteoporosis is disease stage. Elevated serum bilirubin and bile acids observed in PBC exert deleterious effects on osteoblasts, leading to cellular dysfunction and promoting osteoporotic change. The predominant pathogenic mechanism appears to be osteoblast dysfunction with reduced bone formation, although increased bone resorption may also occur in some cases. Management of osteoporosis in PBC includes vitamin D and calcium supplementation, with bisphosphonates commonly employed. Ursodeoxycholic acid may attenuate bone loss indirectly by improving cholestasis and has been reported to enhance osteoblast activity and survival.